Influence of Intensity of Social Media Against Devotion Pattern, Daily Bible, and Mental Health of Fourth Semester Students of IAKN Kupang - Kawa, Simson Mau; Manu, Sendi Marlina; Tanono, Solly Rosalia; Oematan, Senia Enjelika; Polli, Siska; Tofeto, Vantri; Santi Sole, Adriana Indra (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aims to analyze the impact of social media usage on daily Bible devotion habits and the mental health of fourth-semester students in the Christian Religious Education Study Program at IAKN Kupang. In this digital age, there has been a significant increase in social media usage among Christian students, which may affect their spiritual discipline and mental health. The methodology used in this study is a quantitative approach with a causal explanatory survey design. A total of 45 students became the research sample, taken using a purposive sampling technique. Data were collected through a questionnaire using a Likert scale and analyzed with SPSS software version 26, including descriptive analysis, classical assumption tests, multiple regression, and path analysis. The research findings indicate that the intensity of social media usage has a significant negative impact on daily Bible devotion patterns and mental well-being (β = -0.347; p = 0.002). Daily Bible devotion patterns function as a partial mediator with an indirect effect of -0.189 (p < 0.05). Devotion has a significant positive influence on mental health (β = 0.516; p = 0.000). The regression model successfully explained 58.2% of the variation in mental health (R Square = 0.582). This study concluded that daily Bible devotion serves as a protective factor that can reduce the negative impact of social media.